2007
DOI: 10.3171/spi-07/10/423
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effectiveness of mitomycin C and 5-fluorouracil in the prevention of peridural adhesion after laminectomy

Abstract: Object The effectiveness of the topical application of mitomycin C (MMC) or 5-fluorouracil (5FU) in preventing peridural adhesion after laminectomy was compared in this study. Methods Laminectomies were performed at L-1 in 30 rats. Cotton pads soaked with 0.1 mg/ml MMC, 25 mg/ml 5FU, or 9 mg/ml saline (control) were applied to the operative sites. To evaluate neurological deficits pre- and postoperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…MMC impairs DNA replication and prevents protein synthesis, suppressing the proliferation of fibroblasts and epithelial cells and leading to the decreased development of granulation tissue and reduced scar formation, thereby diminishing the negative impacts of fibroblast proliferation [28,29,30]. Due to the recent increase in relevant studies and clinical trials, MMC has been successfully applied to decrease scar formation during postoperative wound healing in the fields of ophthalmology and spinal surgery [14,31,32]. Because FLS are homologous to fibroblasts, the primary objective of this experimental study was to investigate the effect of MMC on the apoptosis of FLS derived from RA patients and the mechanism underlying MMC-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMC impairs DNA replication and prevents protein synthesis, suppressing the proliferation of fibroblasts and epithelial cells and leading to the decreased development of granulation tissue and reduced scar formation, thereby diminishing the negative impacts of fibroblast proliferation [28,29,30]. Due to the recent increase in relevant studies and clinical trials, MMC has been successfully applied to decrease scar formation during postoperative wound healing in the fields of ophthalmology and spinal surgery [14,31,32]. Because FLS are homologous to fibroblasts, the primary objective of this experimental study was to investigate the effect of MMC on the apoptosis of FLS derived from RA patients and the mechanism underlying MMC-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multiple studies have shown that MMC inhibits fibroblast proliferation and induces fibroblast apoptosis [11,12]. Moreover, our previous studies have demonstrated that topical MMC application may inhibit cell proliferation and induce apoptosis in epidural scar fibroblasts, thereby preventing peridural adhesion after laminectomy [13,14]. However, whether MMC inhibits human RA FLS proliferation or induces the apoptosis of these cells has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison of the experimental group with the negative control group, it turned out that the experimental group's scores for both gross and histological adhesion were lower than those of the negative control group. There was no statistical significance in the gross score (P = 0.63), but there was statistical significance in Table 1 Rydell standard [14][15][16] Grade 0 Peridural scar tissue was not adherent to the dura meter Grade 1 Peridural scar tissue was adherent to the dura but easily dissected Grade 2 Peridural scar tissue was adherent to the dura, and there was difficulty in dissecting it without disrupting the dura Grade 3 Peridural scar tissue was firmly adherent to the dura and could not be dissected the histological score (P = 0.04). In comparison between the experimental group and the positive control group, there was no significant difference both in the scores of gross adhesion and histological adhesion (P = 1.00, 0.33, Fig.…”
Section: Week Evaluationmentioning
confidence: 99%
“…After the paraspinal muscle was gently removed, the laminectomy site was probed with a microforcep. The amount of adhesion was judged based on the Rydell standard (Table 1) [14][15][16]. When surrounding bones overgrew into the surgical site, making it impossible to re-expose the dura, it was judged as complete adhesion.…”
Section: Evaluation Of Gross Adhesionmentioning
confidence: 99%
“…Moreover, another one study showed that free adipose tissue used to prevent epidural fibrosis in 99 patients who underwent surgical practise because of lumbar disc herniation (LDH) was clinically ineffective (12,14,30). In another study, the efficacy of the substance used to prevent epidural fibrosis following experimental laminectomy has been investigated via macroscopic evaluation, histopathological fibrosis classification, fibroblast count, and biochemical hydroxyproline levels (29). There was not any obvious adhesion in the rats of mitomycin-C (MMC) group, but severe peridural adhesions were found in those in the 5-fluorouracil (5FU) and control groups.…”
Section: Histopathological Resultsmentioning
confidence: 99%